Chemical Constituents from the Root of Tripterygium wilfordii - Hu, Pan-Yong; Zhang, Di; Pu, She-Ban; Li, Zhen-Lin; Zhou, Hong-Hua (Asian Journal of Chemistry, 2014)
In this paper, the chemical constituents from the root of Tripterygium wilfordii were isolated and characterized. Isolation and purification were carried out on the column chromatography of silica gel and Sephadex LH-20. Fourteen compounds were isolated and identified as (2S,3R,4E,8E,2R)-2-(2'-hydroxyhexadec anoyl) amino-4,8-octadeca diene-1,3-diol (1), soya-cerebrosideI and soya-cerebroside II (2 mixture), adenosine (3), b-sitosterol-palmitate (4) and monopalmitin (5), triptohairic acid (6), hypolide (7), wilforlide B (8), wilforlide A (9), cangoronine (10), salaspermic acid (11), orthosphenic acid (12), 3-hydroxy-2-oxo-3-friedeien- 20-a-carboxylic acid (13), 3b-22a-dihydroxyolean-12-en-29-oic acid (14).